Lack of standards in evaluating YouTube health videos - Boté, Juan-José (Revista Cubana de Información en Ciencias de la Salud, 2019)
This paper is a systematised literature review of YouTube research in health with the aim of identify the different keyword search strategies, retrieval strategies and scoring systems to assess video content. A total of 176 peer-reviewed papers about video content analysis and video evaluation were extracted from the PubMed database. Concerning keyword search strategy, 16 papers (9.09 %) reported that search terms were obtained from tools like Google Trends or other sources. In just one paper, a librarian was included in the research team. Manual retrieval is a common technique, and just four studies (2.27 %) reported using a different methodology. Manual retrieval also produces YouTube algorithm dependencies and consequently obtains biased results. Most other methodologies to analyse video content are based on written medical guidelines instead of video because a standard methodology is lacking. For several reasons, reliability cannot be verified. In addition, because studies cannot be repeated, the results cannot be verified and compared. This paper reports some guidelines to improve research on YouTube, including guidelines to avoid YouTube dependencies and scoring system issues.